Pengaruh Penerapan Good Corporate Governance dan Corporate Social Responsibility terhadap Kinerja Keuangan Perusahaan - Safira Putri Cahyaningrum; Kartika Hendra Titisari; Agni Astungkara (Owner : Riset dan Jurnal Akuntansi, 2022)
The purpose of this analysis is to investigate whether good corporate governance and corporate social responsibility have an influence on the financial performance of a Manufacturing company that are registered on the Indonesia Stock Exchange. This study provides an overview of the affect of corporate governance and corporate social responsibility on a corporation’s financial performance. And in  this case, institutional assets, independent commissioners, and audit committees are used to assess corporate governance. Quantitive method with purposive sampling use in this study. A sampel of 37 manufacturing companies was obtained from the above sampling, with a total of 155 observations reported on the Indonesia Stock Exchange during 2017 until 2021. The multiple linear regression analysis system is used in this data analysis technique. The findings revealed that corporate governance as proxied through  of institutional assets had no large influence on the financial performance. Futher findings revealed that corporate governance as proxied through the audit committee had no large influence on the financial performance of the company. Meanwhile, corporate governance as proxied through the independent board of commissioners has a large affect on a company’s financial performance. The fndings above also revealed that corporate social responsibility has a no discernible affect on the company’s financial performance.